Flame-retardant high-strength composite cable material and preparation method thereof
By using low-density polyethylene, ethylene-octene copolymer, composite polysiloxane and modified magnesium hydroxide in composite cable materials, combined with modified expandable graphite and starch to build a flame retardant system, the traditional solution is solved The problem of insufficient mechanical strength and flame retardant performance of composite cable materials achieves higher mechanical properties and lower smoke density.
Patent Information
- Application Number
- CN202411596239.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When traditional composite cable materials are reinforced with expandable graphite, the mechanical strength and flame retardant properties need to be further improved, and traditional flame retardant additives will produce a large amount of smoke when burned, posing a threat to the environment and personnel safety.
Low-density polyethylene is used as the resin matrix, ethylene-octene copolymer is the compatibility agent, composite polysiloxane is the reinforcement matrix, diisopropyl peroxide is the catalyst, modified magnesium hydroxide is the reinforcement auxiliary agent, through steam High-temperature steaming promotes cross-linking, and combines modified expandable graphite, modified starch and polysiloxane to build a flame retardant system to improve mechanical and flame retardant properties.
It significantly improves the mechanical properties and flame retardant properties of composite cable materials, delays thermal degradation and combustion speed, reduces smoke density, enhances the mechanical strength and thermal stability of the carbon layer, and improves the overall performance of the material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable material processing, and in particular to a flame-retardant high-strength composite cable material and a preparation method thereof. Background Art
[0002] With the rapid development of the electric power industry, the demand for cables, as an important carrier for power transmission and signal transmission, is increasing. At the same time, people have higher and higher requirements on the performance of cables, especially in terms of flame retardancy and strength. In many occasions, such as high-rise buildings, subways, power stations, etc., the flame retardancy of cables is crucial. Traditional cable materials often use halogen-containing flame retardants to improve the flame retardancy, but these flame retardants will release a lot of smoke and toxic gases when burning, causing serious harm to the environment and human health. Therefore, the development of halogen-free, low-smoke, non-toxic flame-retardant cable materials has become a development trend in the industry.
[0003] Composite cable materials refer to materials used as insulating materials and sheaths in the cable manufacturing process. Their performance directly affects the performance and safety of the cable. Expandable graphite is a material with excellent thermal conductivity and high temperature resistance. It is usually used in flame retardant materials because its unique structure can expand to form pores when heated, effectively isolating oxygen and achieving good flame retardant effects. At the same time, graphite also has high mechanical strength, which can provide better mechanical strength for composite cable materials.
[0004] In the preparation process of traditional expandable graphite reinforced composite cable materials, the cable materials are usually prepared by directly mixing the resin matrix with expandable graphite. However, the polarity of expandable graphite and low-density polyethylene is quite different, the interfacial tension between expandable graphite and low-density polyethylene is large, and the graphite particles are difficult to be evenly distributed in the low-density polyethylene matrix. In addition, the degree of cross-linking between the expandable graphite and the constituent molecules of the composite cable material is low, resulting in poor mechanical properties of the expandable graphite reinforced low-density polyethylene cable material. Although expandable graphite can improve the flame retardant properties of the cable material to a certain extent, the flame retardant properties of the cable material are limited by the single expandable graphite. It is usually compounded with other flame retardant additives to improve the flame retardant properties of the material. Traditional flame retardant additives will produce a large amount of smoke during combustion or smoldering, posing a threat to the environment and personnel safety. The flame retardant properties of the composite cable material need to be further improved.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a flame retardant high-strength composite cable material and a preparation method thereof, which is used to solve the technical problem in the prior art that the mechanical strength and flame retardant properties of the composite cable material need to be further improved when the composite cable material is reinforced with expandable graphite.
[0007] The purpose of the present invention can be achieved through the following technical solutions: A flame-retardant high-strength composite cable material, comprising the following components in parts by weight: 100 parts of low-density polyethylene, 20-30 parts of ethylene-octene copolymer, 25-35 parts of composite polysiloxane, 1-1.5 parts of dicumyl peroxide, 3-5 parts of auxiliary additives and 10-14 parts of modified magnesium hydroxide; The composite polysiloxane is processed by the following steps: A1, 5-hexenyltrimethoxysilane, octamethyl silicone oil, 2-[8-(trimethoxysilyl)octyl]-oxirane, and anhydrous ethanol were added to a reaction kettle and stirred, the temperature of the reaction kettle was raised to reflux, potassium hydroxide solution was added to the reaction kettle, and the reaction was kept warm for 6-8 hours, and polysiloxane was obtained by post-treatment; The synthetic reaction principle of polysiloxane is: Under the catalytic action of an alkaline environment, the methoxysilane groups in 5-hexenyltrimethoxysilane and 2-[8-(trimethoxysilyl)octyl]-ethylene oxide undergo a hydrolysis reaction to generate silanol groups, and the silanol groups generated by the hydrolysis undergo a condensation reaction to form a siloxane bond, while releasing water molecules. As the reaction proceeds, multiple siloxane monomers are linked together through a condensation reaction to form a high molecular weight polysiloxane. Octamethyl silicone oil, as a high molecular weight component, may condense with other monomers through its siloxane bond to further promote the formation of polysiloxane, and a polysiloxane modified with an epoxy group and an unsaturated olefin double bond is prepared.
[0008] A2. Add modified expandable graphite, modified starch, polysiloxane, N,N-dimethylformamide and catalyst into a reactor and stir. Raise the temperature of the reactor to 80-90° C. and keep the reaction temperature for 6-8 hours. Post-treat to obtain composite polysiloxane.
[0009] The synthetic reaction principle of composite polysiloxane is: The imine groups on the composite hierarchical structure of the externally activated boehmite and phosphorus of the modified expandable graphite and the active oxygen-containing groups and amino groups on the modified starch can all serve as active sites for the reaction. The epoxy groups on the polysiloxane undergo a nucleophilic addition reaction with the active sites on the modified expandable graphite or modified starch after ring opening under the condition of a catalyst, thereby promoting the mixed cross-linking of the modified expandable graphite, the modified starch and the polysiloxane to form a composite polysiloxane of the modified expandable graphite, the modified starch and the polysiloxane.
[0010] Further, the modified expandable graphite is obtained by processing the following steps: B1, adding nano-boehmite, anhydrous ethanol and KH-550 into a reactor and stirring, raising the temperature of the reactor to 50-60° C., adding sodium hydroxide solution into the reactor, keeping the temperature and stirring for 4-6 hours, and post-treating to obtain activated boehmite; B2. Add trimethylolphosphine oxide, activated boehmite, DMF solution, expandable graphite and catalyst into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 70-80°C. Add a crosslinking agent dropwise into the reactor and keep the temperature for 4-6 hours. Add sodium hydroxide solution into the reactor and keep the temperature for 3-5 hours. Post-treat to obtain modified expandable graphite.
[0011] The synthetic reaction principle of modified expandable graphite is: The siloxane bonds on KH-550 are hydrolyzed under an alkaline environment to form silanol groups that react with the active groups on the surface of the nano-boehmite, forming a KH-550 coating modification on the outside of the nano-boehmite to prepare activated boehmite. After the activated boehmite, trihydroxymethylphosphine oxide and a cross-linking agent are mixed with expandable graphite, the active groups on the activated boehmite and trihydroxymethylphosphine oxide react with the cross-linking agent to form a composite structure of activated boehmite and phosphorus copolymerization. In an alkaline environment, the siloxane bonds in the cross-linking agent are further promoted to be hydrolyzed to form a connection modification with the surface of the expandable graphite, and the composite hierarchical structure of the activated boehmite and phosphorus is stably modified on the outside of the expandable graphite to prepare modified expandable graphite.
[0012] Furthermore, the preparation method of the modified starch is: adding soluble starch and phosphoric acid into a reactor and stirring, raising the temperature of the reactor to 95-100°C, keeping the temperature for reaction for 2-3 hours, adding melamine solution dropwise into the reactor, keeping the temperature for reaction for 40-60 minutes, and post-treating to obtain the modified starch.
[0013] The synthetic reaction principle of modified starch is: Under high temperature conditions, phosphoric acid reacts with the hydroxyl groups in the soluble starch molecules to form phosphate bonds. The amino groups in the melamine molecules can form hydrogen bonds with the phosphate groups in the starch molecules, thereby enhancing the interaction between starch and melamine. The melamine molecules are then inserted into the starch molecules to modify them, thereby preparing modified starch.
[0014] Further, the modified magnesium hydroxide is processed by the following steps: C1. Add nano magnesium hydroxide, anhydrous ethanol and KH-550 into a reactor and stir. Raise the temperature of the reactor to 50-60° C., add sodium hydroxide solution into the reactor, keep the temperature for 4-6 hours, and perform post-treatment to obtain pre-treated magnesium hydroxide. C2, adding pre-treated magnesium hydroxide, tetrahydrofuran, 1,2-epoxy-5-hexene and pyridine into a reaction kettle and stirring, raising the temperature of the reaction kettle to reflux the system, keeping the temperature for 6-8 hours, and post-treating to obtain activated magnesium hydroxide; C3. Add activated magnesium hydroxide and tetrahydrofuran into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 45-55°C. Add isocyanatepropyltriethoxysilane into the reactor and keep the temperature for 2-3h. Post-treat to obtain modified magnesium hydroxide.
[0015] The synthetic reaction principle of modified magnesium hydroxide is: The surface of nano-magnesium hydroxide is modified by coating with KH-550 to prepare pre-treated magnesium hydroxide. Under the condition of pyridine as a catalyst, the epoxy ring on 1,2-epoxy-5-hexene undergoes a nucleophilic addition reaction with the amino group modified on the surface of the pre-treated magnesium hydroxide to form activated magnesium hydroxide modified with hydroxyl groups and unsaturated olefins. The isocyanate group on isocyanatepropyltriethoxysilane can undergo a condensation reaction with the hydroxyl group on the surface of the activated magnesium hydroxide, and the isocyanatepropyltriethoxysilane is grafted and modified onto the activated magnesium hydroxide, forming a triethoxysilane modification on the outside of the activated magnesium hydroxide to prepare modified magnesium hydroxide.
[0016] Further, in step A1, the amount ratio of 5-hexenyltrimethoxysilane, octamethyl silicone oil, 2-[8-(trimethoxysilyl)octyl]-ethylene oxide, anhydrous ethanol and potassium hydroxide solution is 2g:4-6g:2-3g:60mL:10mL, the concentration of the potassium hydroxide solution is 1-2mol / L, and the post-treatment includes: after the reaction is completed, the solvent is evaporated under reduced pressure, toluene and purified water are added to the reactor, stirred for 10-20min, allowed to stand for separation, and the organic phase After washing with purified water for 3 times, the mixture is transferred to a rotary evaporator at a temperature of 75-85°C, and the solvent is evaporated under reduced pressure to obtain polysiloxane; in step A2, the amount ratio of the modified expandable graphite, modified starch, polysiloxane, N,N-dimethylformamide and catalyst is 5-6g:1.8-2.4g:9-10g:40mL:0.2g, the catalyst is pyridine, and the post-treatment includes: after the reaction is completed, the reactor is kept at 90-100°C, and the solvent is evaporated under reduced pressure to obtain a composite polysiloxane.
[0017] Further, in step B1, the amount ratio of the nano-boehmite, anhydrous ethanol, KH-550 and sodium hydroxide solution is 5g:40mL:1.8-2.2g:15mL, the concentration of the sodium hydroxide solution is 0.8-1.2mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 70-80°C and dried to constant weight to obtain activated boehmite; in step B2, the amount ratio of the trihydroxymethylphosphine oxide, activated boehmite, DMF solution, expandable graphite, catalyst, cross-linking agent and sodium hydroxide solution is 0.3-0.4g:0.8 g:60mL:7g:0.01g:2g:10mL, the DMF solution is composed of N,N-dimethylformamide and dodecylphenol polyoxyethylene ether in a dosage ratio of 1g:50mL, the catalyst is dibutyltin dilaurate, the cross-linking agent is composed of isocyanatepropyltriethoxysilane and diphenylmethane-4,4'-diisocyanate in a weight ratio of 1:3, the concentration of the sodium hydroxide solution is 0.3-0.6mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter is filtered, the filter cake is washed with purified water until it is neutral and then dried, the filter cake is transferred to a drying oven at a temperature of 70-80°C, and dried to constant weight to obtain modified expandable graphite.
[0018] Furthermore, the dosage ratio of the soluble starch, phosphoric acid and melamine solution is 2g:15mL:3g, the concentration of the phosphoric acid is 12-14mol / L, the melamine solution is obtained by mixing melamine and purified water at a dosage ratio of 1g:4mL and then uniformly dispersing them, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed 3 times with a 60wt% ethanol solution and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain modified starch.
[0019] Further, in step C1, the amount ratio of the nano magnesium hydroxide, anhydrous ethanol, KH-550 and sodium hydroxide solution is 5g:30mL:1.5-2.5g:10mL, the concentration of the sodium hydroxide solution is 1-2mol / L, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C and dried to constant weight to obtain the pre-treatment magnesium hydroxide; in step C2, the amount ratio of the pre-treatment magnesium hydroxide, tetrahydrofuran, 1,2-epoxy-5-hexene and pyridine is 5g:40mL :3g:0.2g, the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration, the filter cake is washed with purified water for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain activated magnesium hydroxide; in step C3, the amount ratio of the activated magnesium hydroxide, tetrahydrofuran and isocyanatepropyltriethoxysilane is 5g:40mL:3g, the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, suction filtration, the filter cake is washed with tetrahydrofuran for 3 times and then dried, the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain modified magnesium hydroxide.
[0020] A method for preparing a flame retardant high-strength composite cable material comprises the following steps: S1. Mix low-density polyethylene, ethylene-octene copolymer, composite polysiloxane, dicumyl peroxide and auxiliary additives, add them to a torque rheometer at a temperature of 170-180° C., melt-mix for 10-15 minutes, add modified magnesium hydroxide to the torque rheometer, melt-mix for 20-30 minutes, and obtain a mixture; S2. Transfer the mixed material to a flat plate vulcanizer, set the temperature of the flat plate vulcanizer to 175-185°C, the pressure to 12-15MPa, and vulcanize for 20-30min. Place it in a steam environment and steam-cure it at high temperature for 6-8h to obtain a composite cable material.
[0021] Furthermore, the auxiliary additives are composed of a dispersant, a lubricant, an antioxidant, a light stabilizer and an antistatic agent in a weight ratio of 5:3:4:2:2, the dispersant is stearate, the lubricant is liquid paraffin, the antioxidant is one or more of antioxidant D, antioxidant CPPD, antioxidant IPPD, and antioxidant H, the light stabilizer is ultraviolet absorber UV-1164 or ultraviolet absorber 234, and the antistatic agent is sodium p-nonylphenoxypropyl sulfonate.
[0022] The present invention has the following beneficial effects: 1. The flame-retardant high-strength composite cable material of the present invention is prepared by selecting low-density polyethylene as a resin matrix and ethylene-octene copolymer as a compatibilizer. The molecular chain of the ethylene-octene copolymer contains octene units, which can destroy the crystalline structure of polyethylene, form elastic soft segments, and promote good compatibility between polyethylene segments and polysiloxane segments. The present invention uses composite polysiloxane as a reinforcing matrix and dicumyl peroxide as a catalyst to promote the cross-linking bonding degree between the resin matrix and the reinforcing matrix. Modified magnesium hydroxide is used as a reinforcing auxiliary agent. After uniformly mixing it with the resin matrix, the modified magnesium hydroxide is steamed at a high temperature to promote the hydrolysis of triethoxysilane modified on the modified magnesium hydroxide and condensation with other active groups in the material, further improving the crosslinking degree of the composite cable material, so that the composite cable material has good mechanical properties. The composite polysiloxane is obtained by compounding modified expandable graphite, modified starch and polysiloxane. Through the mutual cooperation between the composite polysiloxane and the modified magnesium hydroxide, an expandable flame-retardant system is constructed in the composite cable material, thereby improving the flame-retardant performance of the composite cable material.
[0023] 2. The flame-retardant high-strength composite cable material of the present invention is prepared by selecting expandable graphite as a matrix, adopting nano-boehmite and trimethylol phosphorus oxide as modified raw materials, and forming a composite hierarchical structure of activated boehmite and phosphorus on the outside of the expandable graphite under the action of a cross-linking agent. The modified expandable graphite can expand rapidly at high temperatures to form one or more layers of dense and stable expanded carbon layers, which cover the surface of the polyolefin material, effectively isolate the heat transfer between the flame and the substrate, reduce the temperature of the material surface, thereby delaying the thermal degradation and combustion rate of the material, and the addition of nano-boehmite and trimethylol phosphorus oxide not only enhances the mechanical strength of the carbon layer, but also improves its thermal stability and density, making the carbon layer more difficult to be destroyed at high temperatures, thereby maintaining its heat insulation effect for a longer time, and the phosphorus element in the trimethylol phosphorus oxide is effective in burning. During the calcination process, the carbonization reaction of the polyolefin material can be catalyzed to promote the formation of more carbon. These carbons are combined with the carbon layer formed after the modified expandable graphite is expanded, so as to further enhance the flame retardant performance of the material. After the soluble starch is treated with phosphoric acid, it is modified with melamine to form a modified starch with melamine molecules interspersed with the modified starch. The modified starch cooperates with the modified expandable graphite to further promote the carbonization of the material and dilute the combustible gas, thereby jointly improving the flame retardant performance of the material. The polysiloxane has a Si-O-Si inorganic skeleton as the main chain and has excellent heat resistance and carbonization. At high temperature, the polysiloxane can form a stable SiO2 structure as a barrier layer to reduce the diffusion of heat radiation and combustible degradation products. It cooperates with the modified expandable graphite and the modified starch to further improve the flame retardant performance of the material.
[0024] 3. The flame-retardant high-strength composite cable material of the present invention selects magnesium hydroxide as an inorganic matrix of a reinforcing auxiliary agent, modifies and coats the outside of the inorganic matrix to form an organic alkane modification on the outside of the inorganic matrix, and then modifies the surface of the inorganic matrix with isocyanatepropyl triethoxysilane to form a triethoxysilane modification on the outside of the modified magnesium hydroxide. This can not only effectively promote the uniform dispersion of the modified magnesium hydroxide in the polyolefin material, but also introduce unsaturated olefins on the surface of the modified magnesium hydroxide. Under the action of a free radical initiator, the modified magnesium hydroxide can undergo free radical polymerization with the polyolefin material. The triethoxysilane modified on the surface of the modified magnesium hydroxide undergoes condensation with the polyolefin matrix after hydrolysis of the siloxane bonds during curing in a high-temperature water environment, forming a three-dimensional network crosslinking in the composite cable material, thereby improving the mechanical properties of the composite polyolefin cable material. The magnesium hydroxide can also form a synergistic flame retardant system with modified expandable graphite and modified starch to further improve the flame retardant properties of the composite cable material. DETAILED DESCRIPTION
[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0026] This embodiment provides a method for preparing a flame retardant high-strength composite cable material, comprising the following steps: S1. Preparation of modified expandable graphite Weigh: 50 g of nano-boehmite, 400 mL of anhydrous ethanol and 18 g of KH-550, add them into a reactor and stir, raise the temperature of the reactor to 50°C, add 150 mL of 0.8 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 4 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, dry to constant weight, and obtain activated boehmite; N,N-dimethylformamide and dodecylphenol polyoxyethylene ether were mixed uniformly at a dosage ratio of 1 g:50 mL to obtain a DMF solution; Propyl triethoxysilane and diphenylmethane-4,4'-diisocyanate are mixed uniformly in a weight ratio of 1:3 to obtain a crosslinking agent; Weigh: 30 g of trimethylolphosphine oxide, 80 g of activated boehmite, 6000 mL of DMF solution, 700 g of expandable graphite and 1 g of dibutyltin dilaurate, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 70°C, add 200 g of a cross-linking agent dropwise into the reactor, keep the temperature for 4 hours, add 1000 mL of 0.3 mol / L sodium hydroxide solution into the reactor, keep the temperature for 3 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at 70°C, dry to constant weight, and obtain modified expandable graphite.
[0027] S2. Preparation of modified starch Melamine and purified water were mixed in a dosage ratio of 1 g:4 mL and then uniformly dispersed to obtain a melamine solution; Weigh: 200 g of soluble starch and 1500 mL of 12 mol / L phosphoric acid are added to a reactor and stirred. The temperature of the reactor is raised to 95°C and kept warm for 2 hours. 300 g of melamine solution is added dropwise to the reactor and kept warm for 40 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature and filtered. The filter cake is washed three times with 60 wt% ethanol solution and then dried. The filter cake is transferred to a drying oven at 60°C and dried to constant weight to obtain modified starch.
[0028] S3. Preparation of composite polysiloxane Weigh: 20 g of 5-hexenyltrimethoxysilane, 40 g of octamethyl silicone oil, 20 g of 2-[8-(trimethoxysilyl)octyl]-oxirane, and 600 mL of anhydrous ethanol, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 100 mL of 1 mol / L potassium hydroxide solution to the reactor, keep the temperature for 6 hours, after the reaction is completed, evaporate the solvent under reduced pressure, add 600 mL of toluene and 200 mL of purified water to the reactor, stir for 10 minutes, stand for separation, wash the organic phase with purified water 3 times, transfer it to a rotary evaporator at a temperature of 75°C, and evaporate the solvent under reduced pressure to obtain polysiloxane; Weigh: 50 g of modified expandable graphite, 18 g of modified starch, 90 g of polysiloxane, 400 mL of N,N-dimethylformamide and 2 g of pyridine, add into a reactor and stir, raise the temperature of the reactor to 80° C., and keep the reaction for 6 hours. After the reaction is completed, keep the reactor at 90° C., and evaporate the solvent under reduced pressure to obtain composite polysiloxane.
[0029] S4. Preparation of modified magnesium hydroxide Weigh: 50 g of nano magnesium hydroxide, 300 mL of anhydrous ethanol and 15 g of KH-550, add them into a reactor and stir, raise the temperature of the reactor to 50°C, add 100 mL of 1 mol / L sodium hydroxide solution into the reactor, and keep the reaction for 4 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 60°C, and dry it to constant weight to obtain the magnesium hydroxide in the previous step; Weigh: 50 g of pre-treated magnesium hydroxide, 400 mL of tetrahydrofuran, 30 g of 1,2-epoxy-5-hexene and 2 g of pyridine, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature to react for 6 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 60°C, and dry to constant weight to obtain activated magnesium hydroxide; Weigh: 50 g of activated magnesium hydroxide and 400 mL of tetrahydrofuran are added to a nitrogen-protected reactor and stirred. The temperature of the reactor is raised to 45°C, 30 g of isocyanatepropyltriethoxysilane is added to the reactor, and the reaction is kept warm for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed 3 times with tetrahydrofuran and then dried. The filter cake is transferred to a drying oven at a temperature of 60°C and dried to constant weight to obtain modified magnesium hydroxide.
[0030] S5, composite cable material Mix sodium stearate, liquid paraffin, antioxidant D, ultraviolet absorber UV-1164 and sodium p-nonylphenoxypropyl sulfonate in a weight ratio of 5:3:4:2:2 to obtain an auxiliary additive; Weigh by weight: 100 parts of low-density polyethylene, 20 parts of ethylene-octene copolymer, 25 parts of composite polysiloxane, 1 part of dicumyl peroxide and 3 parts of auxiliary additives, add to a torque rheometer at a temperature of 170° C., melt-mix for 10 minutes, add 10 parts of modified magnesium hydroxide to the torque rheometer, melt-mix for 20 minutes, and obtain a mixture; The mixed material was transferred to a flat-plate vulcanizer, the temperature of the flat-plate vulcanizer was set to 175°C, the pressure was set to 12MPa, the vulcanization treatment was carried out for 20min, and it was placed in a steam environment and steamed at high temperature for 6h to obtain a composite cable material. Example
[0031] This embodiment provides a method for preparing a flame retardant high-strength composite cable material, comprising the following steps: S1. Preparation of modified expandable graphite Weigh: 50 g of nano-boehmite, 400 mL of anhydrous ethanol and 20 g of KH-550, add them into a reactor and stir, raise the temperature of the reactor to 55°C, add 150 mL of 1.0 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 5 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, dry to constant weight, and obtain activated boehmite; N,N-dimethylformamide and dodecylphenol polyoxyethylene ether were mixed uniformly at a dosage ratio of 1 g:50 mL to obtain a DMF solution; Propyl triethoxysilane and diphenylmethane-4,4'-diisocyanate are mixed uniformly in a weight ratio of 1:3 to obtain a crosslinking agent; Weigh: 35 g of trimethylolphosphine oxide, 80 g of activated boehmite, 6000 mL of DMF solution, 700 g of expandable graphite and 1 g of dibutyltin dilaurate, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 75° C., add 200 g of a crosslinking agent dropwise into the reactor, and keep the temperature for 5 h. Add 1000 mL of 0.45 mol / L sodium hydroxide solution into the reactor and keep the temperature for 4 h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at 75° C., and dry it to constant weight to obtain modified expandable graphite.
[0032] S2. Preparation of modified starch Melamine and purified water were mixed in a dosage ratio of 1 g:4 mL and then uniformly dispersed to obtain a melamine solution; Weigh: 200 g of soluble starch and 1500 mL of 13 mol / L phosphoric acid are added to a reactor and stirred. The temperature of the reactor is raised to 97°C and the reaction is kept warm for 2.5 hours. 300 g of melamine solution is added dropwise to the reactor and the reaction is kept warm for 50 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature and filtered. The filter cake is washed three times with 60 wt% ethanol solution and then dried. The filter cake is transferred to a drying oven at a temperature of 65°C and dried to constant weight to obtain modified starch.
[0033] S3. Preparation of composite polysiloxane Weigh: 20 g of 5-hexenyltrimethoxysilane, 50 g of octamethyl silicone oil, 25 g of 2-[8-(trimethoxysilyl)octyl]-oxirane, and 600 mL of anhydrous ethanol, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 100 mL of 1.5 mol / L potassium hydroxide solution to the reactor, keep the temperature for 7 hours, after the reaction is completed, evaporate the solvent under reduced pressure, add 600 mL of toluene and 200 mL of purified water to the reactor, stir for 15 minutes, stand for separation, wash the organic phase with purified water 3 times, transfer it to a rotary evaporator at a temperature of 80°C, and evaporate the solvent under reduced pressure to obtain polysiloxane; Weigh: 55 g of modified expandable graphite, 21 g of modified starch, 95 g of polysiloxane, 400 mL of N,N-dimethylformamide and 2 g of pyridine, add into a reactor and stir, raise the temperature of the reactor to 85° C., and keep the reaction for 7 hours. After the reaction is completed, keep the reactor at 95° C., and evaporate the solvent under reduced pressure to obtain composite polysiloxane.
[0034] S4. Preparation of modified magnesium hydroxide Weigh: 50 g of nano magnesium hydroxide, 300 mL of anhydrous ethanol and 20 g of KH-550, add them into a reactor and stir, raise the temperature of the reactor to 55°C, add 100 mL of 1.5 mol / L sodium hydroxide solution into the reactor, and keep the reaction for 5 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, and dry it to constant weight to obtain the magnesium hydroxide in the previous step; Weigh: 50 g of pre-treated magnesium hydroxide, 400 mL of tetrahydrofuran, 30 g of 1,2-epoxy-5-hexene and 2 g of pyridine, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, and keep the reaction for 7 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 65° C., and dry to constant weight to obtain activated magnesium hydroxide; Weigh: 50 g of activated magnesium hydroxide and 400 mL of tetrahydrofuran are added to a nitrogen-protected reactor and stirred. The temperature of the reactor is raised to 50°C, 30 g of isocyanatepropyltriethoxysilane is added to the reactor, and the reaction is kept warm for 2.5 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed 3 times with tetrahydrofuran and then dried. The filter cake is transferred to a drying oven at a temperature of 65°C and dried to constant weight to obtain modified magnesium hydroxide.
[0035] S5, composite cable material Calcium stearate, liquid paraffin, antioxidant CPPD, ultraviolet absorber 234 and sodium p-nonylphenoxypropyl sulfonate are uniformly mixed in a weight ratio of 5:3:4:2:2 to obtain an auxiliary additive; Weigh by weight: 100 parts of low-density polyethylene, 25 parts of ethylene-octene copolymer, 30 parts of composite polysiloxane, 1.3 parts of dicumyl peroxide and 4 parts of auxiliary additives, add to a torque rheometer at a temperature of 175° C., melt-mix for 13 minutes, add 12 parts of modified magnesium hydroxide to the torque rheometer, melt-mix for 25 minutes, and obtain a mixture; The mixed material was transferred to a flat-plate vulcanizer, and the temperature and pressure of the flat-plate vulcanizer were set to 180°C and 14 MPa, and the vulcanization treatment was performed for 25 minutes. The mixed material was placed in a steam environment and steamed at high temperature for 7 hours to obtain a composite cable material. Example
[0036] This embodiment provides a method for preparing a flame retardant high-strength composite cable material, comprising the following steps: S1. Preparation of modified expandable graphite Weigh: 50 g of nano-boehmite, 400 mL of anhydrous ethanol and 22 g of KH-550, add them into a reactor and stir, raise the temperature of the reactor to 60°C, add 150 mL of 1.2 mol / L sodium hydroxide solution into the reactor, keep warm and stir for 6 hours, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at a temperature of 80°C, dry to constant weight, and obtain activated boehmite; N,N-dimethylformamide and dodecylphenol polyoxyethylene ether were mixed uniformly at a dosage ratio of 1 g:50 mL to obtain a DMF solution; Propyl triethoxysilane and diphenylmethane-4,4'-diisocyanate are mixed uniformly in a weight ratio of 1:3 to obtain a crosslinking agent; Weigh: 40 g of trimethylolphosphine oxide, 80 g of activated boehmite, 6000 mL of DMF solution, 700 g of expandable graphite and 1 g of dibutyltin dilaurate, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 80° C., add 200 g of a crosslinking agent dropwise into the reactor, and keep the temperature for 6 h. Add 1000 mL of 0.6 mol / L sodium hydroxide solution into the reactor and keep the temperature for 5 h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then drain, transfer the filter cake to a drying oven at 80° C., and dry to constant weight to obtain modified expandable graphite.
[0037] S2. Preparation of modified starch Melamine and purified water were mixed in a dosage ratio of 1 g:4 mL and then uniformly dispersed to obtain a melamine solution; Weigh: 200 g of soluble starch and 1500 mL of 14 mol / L phosphoric acid are added to a reactor and stirred. The temperature of the reactor is raised to 100°C and the reaction is kept warm for 3 hours. 300 g of melamine solution is added dropwise to the reactor and the reaction is kept warm for 60 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature and filtered. The filter cake is washed three times with 60 wt% ethanol solution and then dried. The filter cake is transferred to a drying oven at 70°C and dried to constant weight to obtain modified starch.
[0038] S3. Preparation of composite polysiloxane Weigh: 20 g of 5-hexenyltrimethoxysilane, 60 g of octamethyl silicone oil, 30 g of 2-[8-(trimethoxysilyl)octyl]-oxirane, and 600 mL of anhydrous ethanol, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 100 mL of 2 mol / L potassium hydroxide solution to the reactor, keep the temperature for reaction for 8 h, after the reaction is completed, evaporate the solvent under reduced pressure, add 600 mL of toluene and 200 mL of purified water to the reactor, stir for 20 min, stand for separation, wash the organic phase with purified water 3 times, transfer it to a rotary evaporator at a temperature of 85° C., evaporate the solvent under reduced pressure to obtain polysiloxane; Weigh: 60 g of modified expandable graphite, 24 g of modified starch, 100 g of polysiloxane, 400 mL of N,N-dimethylformamide and 2 g of pyridine, add into a reactor and stir, raise the temperature of the reactor to 90° C., and keep the reaction for 8 hours. After the reaction is completed, keep the reactor at 100° C., and evaporate the solvent under reduced pressure to obtain composite polysiloxane.
[0039] S4. Preparation of modified magnesium hydroxide Weigh: 50 g of nano magnesium hydroxide, 300 mL of anhydrous ethanol and 25 g of KH-550, add them into a reactor and stir, raise the temperature of the reactor to 60°C, add 100 mL of 2 mol / L sodium hydroxide solution into the reactor, and keep the reaction for 6 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and dry it to constant weight to obtain the magnesium hydroxide in the previous step; Weigh: 50 g of pre-treated magnesium hydroxide, 400 mL of tetrahydrofuran, 30 g of 1,2-epoxy-5-hexene and 2 g of pyridine, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, and keep the temperature to react for 8 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and dry to constant weight to obtain activated magnesium hydroxide; Weigh: 50 g of activated magnesium hydroxide and 400 mL of tetrahydrofuran are added to a nitrogen-protected reactor and stirred. The temperature of the reactor is raised to 55° C., 30 g of isocyanatepropyltriethoxysilane is added to the reactor, and the reaction is kept warm for 3 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed 3 times with tetrahydrofuran and then dried. The filter cake is transferred to a drying oven at a temperature of 70° C. and dried to constant weight to obtain modified magnesium hydroxide.
[0040] S5, composite cable material Zinc stearate, liquid paraffin, antioxidant H, ultraviolet absorber UV-1164 and sodium p-nonylphenoxypropyl sulfonate are uniformly mixed in a weight ratio of 5:3:4:2:2 to obtain an auxiliary additive; Weigh by weight: 100 parts of low-density polyethylene, 30 parts of ethylene-octene copolymer, 35 parts of composite polysiloxane, 1.5 parts of dicumyl peroxide and 5 parts of auxiliary additives, add to a torque rheometer at a temperature of 180° C., melt-mix for 15 minutes, add 14 parts of modified magnesium hydroxide to the torque rheometer, melt-mix for 30 minutes, and obtain a mixture; The mixed material was transferred to a flat-plate vulcanizer, and the temperature of the flat-plate vulcanizer was set to 185°C and the pressure to 15 MPa. The vulcanization treatment was performed for 30 minutes. The mixed material was placed in a steam environment and steamed at high temperature for 8 hours to obtain a composite cable material.
[0041] Comparative Example 1 The difference between this comparative example and Example 3 is that step S1 is eliminated, and the modified expandable graphite in step S3 is replaced by the expandable graphite in step S1.
[0042] Comparative Example 2 The difference between this comparative example and Example 3 is that step S2 is eliminated, and the modified starch in step S3 is replaced by the soluble starch in step S2.
[0043] Comparative Example 3 The difference between this comparative example and Example 3 is that step S2 is omitted and no modified starch is added in step S2.
[0044] Comparative Example 4 The difference between this comparative example and Example 3 is that step S4 is eliminated, and the modified magnesium hydroxide in step S5 is replaced by the nano magnesium hydroxide in step S4.
[0045] Performance Test: The tensile strength, elongation at break, thermal extension, oxygen index and smoke density of the composite cable materials prepared in Examples 1-3 and Comparative Examples 1-4 were measured with reference to the standard GB / T 32129-2015 "Halogen-free low-smoke flame-retardant cable materials for wires and cables". The thermal extension performance is the maximum permanent deformation of the test sample after cooling. The specific test results are shown in Table 1 below: Table 1. Performance test data of samples Group Project Tensile strength / MPa Elongation at break / % Thermal extension / % Oxygen index / % Smoke density (flameless) Example 1 38.2 295.8 3.6 71 108 Example 2 38.7 298.4 3.3 73 102 Example 3 38.4 293.6 3.5 70 105 Comparative Example 1 32.4 228.7 5.4 58 128 Comparative Example 2 35.7 283.6 4.1 61 113 Comparative Example 3 36.2 288.8 3.9 52 143 Comparative Example 4 30.9 207.2 7.3 64 121 Data Analysis: A comparative analysis of the data in Table 1 shows that the tensile strength of the composite cable material prepared by the present invention reaches 38.7 MPa, the elongation at break reaches 298.4%, and after the hot extension test, the maximum permanent deformation of the sample after cooling is reduced to 3.3%, the oxygen index of the test piece reaches 73%, and the smoke density (flameless) is reduced to 102. All performance data are better than those of the comparative example, indicating that the present invention uses a composite polysiloxane obtained by compounding modified expandable graphite, modified starch and polysiloxane as a reinforcing material, and a modified magnesium hydroxide containing unsaturated double bonds and modified with triethoxysiloxane as a reinforcing agent to reinforce low-density polyethylene and ethylene-octene copolymer to prepare a composite cable material, which not only effectively improves the flame retardant properties of the composite cable material, but also improves the mechanical properties of the composite cable material.
[0046] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0047] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0048] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A flame retardant high-strength composite cable material, characterized in that: The invention comprises the following components in parts by weight: 100 parts of low-density polyethylene, 20-30 parts of ethylene-octene copolymer, 25-35 parts of composite polysiloxane, 1-1.5 parts of dicumyl peroxide, 3-5 parts of auxiliary additives and 10-14 parts of modified magnesium hydroxide; The composite polysiloxane is processed by the following steps: A1, 5-hexenyltrimethoxysilane, octamethyl silicone oil, 2-[8-(trimethoxysilyl)octyl]-oxirane, and anhydrous ethanol were added to a reaction kettle and stirred, the temperature of the reaction kettle was raised to reflux, potassium hydroxide solution was added to the reaction kettle, and the reaction was kept warm for 6-8 hours, and polysiloxane was obtained by post-treatment; A2, adding modified expandable graphite, modified starch, polysiloxane, N,N-dimethylformamide and catalyst into a reaction kettle and stirring, raising the temperature of the reaction kettle to 80-90° C., keeping the temperature for reaction for 6-8 hours, and post-treating to obtain composite polysiloxane; The modified expandable graphite is processed by the following steps: B1, adding nano-boehmite, anhydrous ethanol and KH-550 into a reactor and stirring, raising the temperature of the reactor to 50-60° C., adding sodium hydroxide solution into the reactor, keeping the temperature and stirring for 4-6 hours, and post-treating to obtain activated boehmite; B2, adding trimethylolphosphine oxide, activated boehmite, DMF solution, expandable graphite and catalyst into a nitrogen-protected reactor and stirring, raising the temperature of the reactor to 70-80° C., adding a crosslinking agent dropwise into the reactor, and keeping the temperature for 4-6 hours, adding sodium hydroxide solution into the reactor, keeping the temperature for 3-5 hours, and post-treating to obtain modified expandable graphite; The preparation method of the modified starch comprises: adding soluble starch and phosphoric acid into a reaction kettle and stirring, raising the temperature of the reaction kettle to 95-100° C., keeping the temperature for reaction for 2-3 hours, adding dropwise melamine solution into the reaction kettle, keeping the temperature for reaction for 40-60 minutes, and post-treating to obtain the modified starch; Modified magnesium hydroxide is processed by the following steps: C1. Add nano magnesium hydroxide, anhydrous ethanol and KH-550 into a reactor and stir. Raise the temperature of the reactor to 50-60° C., add sodium hydroxide solution into the reactor, keep the temperature for 4-6 hours, and perform post-treatment to obtain pre-treated magnesium hydroxide. C2, adding pre-treated magnesium hydroxide, tetrahydrofuran, 1,2-epoxy-5-hexene and pyridine into a reaction kettle and stirring, raising the temperature of the reaction kettle to reflux the system, keeping the temperature for 6-8 hours, and post-treating to obtain activated magnesium hydroxide; C3. Add activated magnesium hydroxide and tetrahydrofuran into a nitrogen-protected reactor and stir. Raise the temperature of the reactor to 45-55°C. Add isocyanatepropyltriethoxysilane into the reactor and keep the temperature for 2-3h. Post-treat to obtain modified magnesium hydroxide.
2. A flame-retardant high-strength composite cable material according to claim 1, characterized in that: In step A1, the amount ratio of 5-hexenyltrimethoxysilane, octamethyl silicone oil, 2-[8-(trimethoxysilyl)octyl]-ethylene oxide, anhydrous ethanol and potassium hydroxide solution is 2g:4-6g:2-3g:60mL:10mL, and the concentration of the potassium hydroxide solution is 1-2mol / L; in step A2, the amount ratio of the modified expandable graphite, modified starch, polysiloxane, N,N-dimethylformamide and catalyst is 5-6g:1.8-2.4g:9-10g:40mL:0.2g, and the catalyst is pyridine.
3. The flame-retardant high-strength composite cable material according to claim 1, characterized in that: In step B1, the dosage ratio of the nano-boehmite, anhydrous ethanol, KH-550 and sodium hydroxide solution is 5g:40mL:1.8-2.2g:15mL, and the concentration of the sodium hydroxide solution is 0.8-1.2mol / L; in step B2, the dosage ratio of the trihydroxymethylphosphine oxide, activated boehmite, DMF solution, expandable graphite, catalyst, cross-linking agent and sodium hydroxide solution is 0.3-0.4g:0.8g:60mL:7g:0.01g:2g:10mL, the DMF solution is composed of N,N-dimethylformamide and dodecylphenol polyoxyethylene ether in a dosage ratio of 1g:50mL, the catalyst is dibutyltin dilaurate, the cross-linking agent is composed of isocyanatepropyltriethoxysilane and diphenylmethane-4,4'-diisocyanate in a weight ratio of 1:3, and the concentration of the sodium hydroxide solution is 0.3-0.6mol / L.
4. The flame-retardant high-strength composite cable material according to claim 1, characterized in that: The dosage ratio of the soluble starch, phosphoric acid and melamine solution is 2g:15mL:3g, the concentration of the phosphoric acid is 12-14mol / L, and the melamine solution is obtained by mixing melamine and purified water at a dosage ratio of 1g:4mL and then uniformly dispersing them.
5. The flame-retardant high-strength composite cable material according to claim 1, characterized in that: In step C1, the dosage ratio of the nano magnesium hydroxide, anhydrous ethanol, KH-550 and sodium hydroxide solution is 5g:30mL:1.5-2.5g:10mL, and the concentration of the sodium hydroxide solution is 1-2mol / L; in step C2, the dosage ratio of the pre-treated magnesium hydroxide, tetrahydrofuran, 1,2-epoxy-5-hexene and pyridine is 5g:40mL:3g:0.2g; in step C3, the dosage ratio of the activated magnesium hydroxide, tetrahydrofuran and isocyanatepropyltriethoxysilane is 5g:40mL:3g.
6. A method for preparing a flame-retardant high-strength composite cable material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Mix low-density polyethylene, ethylene-octene copolymer, composite polysiloxane, dicumyl peroxide and auxiliary additives, add them to a torque rheometer at a temperature of 170-180° C., melt-mix for 10-15 minutes, add modified magnesium hydroxide to the torque rheometer, melt-mix for 20-30 minutes, and obtain a mixture; S2. Transfer the mixed material to a flat plate vulcanizer, set the temperature of the flat plate vulcanizer to 175-185°C, the pressure to 12-15MPa, and vulcanize for 20-30min. Place it in a steam environment and steam-cure it at high temperature for 6-8h to obtain a composite cable material.
7. The method for preparing a flame-retardant high-strength composite cable material according to claim 6, characterized in that: The auxiliary additives are composed of a dispersant, a lubricant, an antioxidant, a light stabilizer and an antistatic agent in a weight ratio of 5:3:4:2:2, the dispersant is stearate, the lubricant is liquid paraffin, the antioxidant is one or more of antioxidant D, antioxidant CPPD, antioxidant IPPD, and antioxidant H, the light stabilizer is an ultraviolet absorber UV-1164 or an ultraviolet absorber 234, and the antistatic agent is sodium p-nonylphenoxypropyl sulfonate.
Citation Information
Patent Citations
Low-smoke halogen-free ceramic polyolefin fire-resistant insulation material and preparation method thereof
CN106674708A
Electret polyetherimide-boehmite composite fiber filter material prepared through electrostatic spinning and preparation method thereof
CN106757483A
Wood-plastic composite material taking silane-modified boehmite as flame retardant and preparation method thereof
CN107446368A
Flexible fireproof pipe for wires and cables and application thereof
CN111825935A
Preparation method of green sustainable chemical-physical synergistic intumescent flame-retardant system
CN113461950A
Cited By
Lightweight flame-retardant EVA foam material and preparation method thereof
CN120648083A
Polyolefin cable material based on graphene composite filler and preparation method thereof
CN121249046A
Copper core and aluminum core plastic insulation power cable and preparation method thereof
CN121885323A
